Synthesis and Characterization of New 5-Fluoroisatin-Chalcone Conjugates with Expected Antimicrobial Activity - Hamza Fadhil Hamza; Mohammed Jawad Al-Mudhafar, May (Iraqi Journal of Pharmaceutical Sciences, 2024)
Pathogenic microorganisms are becoming more and more resistant to antimicrobial agents. So the synthesis of new antimicrobial agents is very important. In this work, new 5-fluoroisatin-chalcone conjugates 5(a–g) were synthesized based on previous research that showed the modifications of the isatin moiety led to the synthesis of many derivatives that have antimicrobial activity. 4-aminoacetophenone reacts with 5-fluoroisatin to form Schiff base (3), which in turn reacts with two different groups of aromatic (carbocyclic and heterocyclic) aldehydes 4(a–g) separately to form the final compounds 5(a–g). Proton-nuclear magnetic resonance (¹H-NMR) and Fourier-transform infrared (FT-IR) spectroscopy were used to confirm the chemical structures of the newly prepared compounds. Finally, the final compounds, 5-fluoroisatin-chalcone conjugates 5(a–g), were screened for their antimicrobial activities and compared with three different references: vancomycin, ciprofloxacin, and fluconazole. They appeared to be good candidates as antibacterial agents against E. coli and S. aureus as well as antifungal agents against C. albicans. In general and for comparison, the antifungal activity of the final compounds 5(a–g) was more potent than their antibacterial activity. Finally, for the antimicrobial activity, the most active compound of these series was compound 5e, while compound 5g was the least active one.